Arylacetylene end capped naphthodithiophene diimide (NDTI)-based semiconductors for air-stable, solution-processed n-channel organic field-effect transistors: Effect of terminal aryl groups on charge transport. (October 2019) - Ran, Huijuan; Chen, Lijuan; Yang, Xueli; Zhang, Jiali; Zhao, Zhen; Han, Ruijun; Duan, Xuewei; Hu, Jian-Yong
Abstract: Solution-processable n-channel organic field-effect transistors (OFETs) are crucial for realizing low-cost, large-area, and all organic logic/complementary circuits. Herein, we present the synthesis, characterization and OFET characteristics of a series of arylacetylene end capped NDTI-based n-channel small molecule semiconductors with four different arylacetylene groups, i.e., thiophenylethynyl (TE, NDTI-BTE), phenylethynyl (PE, NDTI-BPE), 2-pyridinylethynyl (2PdE, NDTI-B2PdE), 4-pyridinylethynyl (4PdE, NDTI-B4PdE). All four NDTIs exhibit excellent solubility behavior in common organic solvents. Electrochemical and optical studies reveal that the introduction of the arylacetylene groups at the thiophene α-positions of NDTI endowed these molecules have sufficiently low-lying LUMO energy levels from −4.12 to −4.24 eV, suitable for better air-stable electron transport. Under ambient atmosphere, we found that solution-processed bottom-gate top-contact (BGTC) transistors based on 120 °C-annealed thin-films of these NDTIs exhibit the best performance with the maximum electron mobilities of 0.049, 0.023, 0.011 and 0.033 cm 2  V −1  s −1 for NDTI-BTE, NDTI-BPE, NDTI-B2PdE and NDTI-B4PdE, respectively, due to better thin film microstructures. AFM measurements reveal that the spin-coated films of these materials exhibited quite smooth and uniform morphology although these are small molecules forming crystalline structures. These results clearly demonstrate that arylacetylene groups are potential functional moieties for developing ambient-stable solution-processable small molecular electron-transporting materials for printable organic electronics. Graphical abstract: Image 1 Highlights: ➢ Arylacetylene end capped NDTI-based n-type semiconductors were reported. ➢ These molecules have sufficiently low-lying LUMOs from −4.12 to −4.24 eV, suitable for better air-stable electron transport. ➢ The highest electron mobility up to 0.049 cm 2  V −1  s −1 was obtained in spin-coated BGTC OFET under ambient conditions.